KEDUDUKAN MAHAR DALAM AKAD NIKAH PERSPEKTIF IMAM MALIK DAN IMAM SYAFI’I - Muhamad Rizki Akmal; Idarotul Nginayah (Fakultas Syariah, Prodi Ahwal As Syakhsiyah (AS) Universitas Nahdlatul Ulama Al-Ghazali (UNUGHA) Cilacap, 2022)
Dowry is one of the virtues of the Islamic religion in protecting and honoring women by giving them the rights they demand in marriage in the form of a dowry, the size of which is determined by the agreement of both parties. The aim of this research is to find out Imam Malik's opinion about the position of the dowry in the marriage contract and to find out Imam Syafi'i's opinion about the position of the dowry in the marriage contract. The research method used is a type of library research (libery research), namely a series of activities relating to methods of collecting library data, reading and taking notes and processing research materials. The research results tend to be more in line with Imam Syafi'I's opinion because his opinion is final and there is no debate regarding the dowry, namely as a legal condition for marriage, especially as Indonesian citizens, almost the majority adhere to the Imam Syafi'I school of thought, Imam Syafi'I's opinion is also largely included. in the compilation of Islamic law in Indonesia. Because his flexible opinion is easy to accept and is not burdensome for the Indonesian people.